2015
DOI: 10.1039/c5nr03828f
|View full text |Cite
|
Sign up to set email alerts
|

Easy conversion of protein-rich enoki mushroom biomass to a nitrogen-doped carbon nanomaterial as a promising metal-free catalyst for oxygen reduction reaction

Abstract: The search for low-cost, highly active, and stable catalysts to replace the Pt-based catalysts for oxygen reduction reaction (ORR) has recently become a topic of interest. Herein, we report a new strategy to design a nitrogen-doped carbon nanomaterial for use as a metal-free ORR catalyst based on facile pyrolysis of protein-rich enoki mushroom (Flammulina velutipes) biomass at 900 °C with carbon nanotubes as a conductive agent and inserting matrix. We found that various forms of nitrogen (nitrile, pyrrolic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(68 citation statements)
references
References 42 publications
6
61
1
Order By: Relevance
“…For further study, we compared the ORR catalytic property of N-BC@G-900 with other catalysts [13,14,17,21,35,36,38], as displayed in Table S1 (online). Our results are comparable with those of the best N-doped carbon catalysts reported to date in terms of E ORR , half-wave potential, average electron transfer number (n) and limited current density, but the BET surface area of the N-BC@G-900 catalyst is much lower than that of numerous nitrogen-doped carbon catalysts [16,33,34]. In fact, the major reason for the electrocatalytic activity enhancement is the density of surface active sites rather than the total surface area, although the significance of the BET specific surface area cannot be ruled out totally [31].…”
Section: Electrocatalytic Performance For Oxygen Reductionsupporting
confidence: 92%
See 2 more Smart Citations
“…For further study, we compared the ORR catalytic property of N-BC@G-900 with other catalysts [13,14,17,21,35,36,38], as displayed in Table S1 (online). Our results are comparable with those of the best N-doped carbon catalysts reported to date in terms of E ORR , half-wave potential, average electron transfer number (n) and limited current density, but the BET surface area of the N-BC@G-900 catalyst is much lower than that of numerous nitrogen-doped carbon catalysts [16,33,34]. In fact, the major reason for the electrocatalytic activity enhancement is the density of surface active sites rather than the total surface area, although the significance of the BET specific surface area cannot be ruled out totally [31].…”
Section: Electrocatalytic Performance For Oxygen Reductionsupporting
confidence: 92%
“…Nie et al [45] proposed that The ORR polarization curves of N-BC@G-900 and Pt/C-ETK (inset) before and after undergoing N 2 cycling tests in O 2 -saturated 0.1 mol/L KOH at a rotation rate of 1,600 r/min the planar N on the surface of carbon-based catalysts is closely contacted with an efficient electron transfer pathway and further assured the rapid free-flowing electron transport to the ORR process. The results of our group [21,33] also showed that the pyrrolic N might be a key configuration of catalytic active sites and function as an effective promoter to the ORR. In addition, Rao et al [42] significantly found that the electrocatalytic activity of N-doped carbon-based catalysts might be usually related to the pyridinic N. Guo et al [46] further clarified the ORR active site by using newly designed graphite model catalysts with well-defined p conjugation and well-controlled doping of N species, and found that the active sites in N-doped carbon materials are carbon atoms with Lewis basicity next to pyridinic N. Therefore, we can reasonably conclude that the planar N (pyridinic-N and pyrrolic-N) may be the N functionality that is most responsible for maintaining the ORR catalytic activity, and the graphitic-N functionality can play an essential role in the improvement of the catalytic activity in alkaline medium.…”
Section: Electrocatalytic Performance For Oxygen Reductionmentioning
confidence: 78%
See 1 more Smart Citation
“…As seen from Figure 1b, all Raman spectra are deconvoluted into two components, and the characteristic “D” and “G” peaks can be found, respectively. According to the previously reported results [13,17], the intensity ratio of D/G ( I D / I G ) is closely related to the amount of structural defects on the catalyst surface. Hence, in the present work, the I D / I G ratios are obtained in N-C@CNT and N-C@CNT-Fe, i.e., 0.78 vs. 0.83, suggesting a lower graphitization degree and more defected structures on the surface of N-C@CNT-Fe, implying the surface doping of more nitrogen atoms on the nitrogen-doped carbon layers.…”
Section: Resultsmentioning
confidence: 78%
“…For N-C@CNT, two amorphous-carbon peaks with 2θ values of ~25° and ~44° can be identified, which are attributed to the (002) and (101) of graphitic planes, respectively [13]. In addition, a finding is that the width of two diffraction peaks increases largely, compared with the XRD pattern of CNT (inset in Figure 1a), which may be explained by the influence of lower graphitization degree [17,18]. However, the XRD pattern of N-C@CNT-Fe exhibits more complex phase composition, and a series of sharp peaks are displayed at 30.2°, 35.6°, 43.2°, 53.6°, 57.1° and 62.7°, which can be ascribed to crystalline Fe 3 O 4 phases according to the XRD card (No.…”
Section: Resultsmentioning
confidence: 99%